h - Pientka, Brigitte; Tinelli, Cesare; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This open access book constitutes the proceedings of the 29th International Conference on Automated Deduction, CADE 29, which took place in Rome, Italy, during July 2023. .
Certified Core-Guided MaxSAT Solving -- Superposition with Delayed Unification -- On Incremental Pre-processing for SMT -- Verified Given Clause Procedures -- QSMA: A New Algorithm for Quantified Satisfiability Modulo Theory and Assignment -- Uniform Substitution for Dynamic Logic with Communicating Hybrid Programs -- An Isabelle/HOL Formalization of the SCL(FOL) Calculus -- SCL(FOL) Can Simulate Non-Redundant Superposition Clause Learning -- Formal Reasoning about Influence in Natural Sciences Experiments -- A Theory of Cartesian Arrays (with Applications in Quantum Circuit Verification) -- SAT-Based Subsumption Resolution -- A more Pragmatic CDCL for IsaSAT and targetting LLVM (Short Paper) -- Proving Non-Termination by Acceleration Driven Clause Learning (Short Paper) -- COOL 2 - A Generic Reasoner for Modal Fixpoint Logics (System Description) -- Choose your Colour: Tree Interpolation for Quantified Formulas in SMT -- Proving Termination of C Programs with Lists -- Reasoning about Regular Properties: A Comparative Study -- Program Synthesis in Saturation -- A Uniform Formalisation of Three-Valued Logics in Bisequent Calculus -- Proving Almost-Sure Innermost Termination of Probabilistic Term Rewriting Using Dependency Pairs -- Verification of NP-hardness Reduction Functions for Exact Lattice Problems -- Buy One Get 14 Free: Evaluating Local Reductions for Modal Logic -- Left-Linear Completion with AC Axioms -- On P -interpolation in local theory extensions and applications to the study of interpolation in the description logics EL, EL+ -- Theorem Proving in Dependently-Typed Higher-Order Logic -- Towards Fast Nominal Anti-Unification of Letrec-Expressions -- Confluence Criteria for Logically Constrained Rewrite Systems -- Towards a Verified Tableau Prover for a Quantifier-Free Fragment of Set Theory -- An Experimental Pipeline for Automated Reasoning in Natural Language (Short paper) -- Combining Combination Properties: An Analysis of Stable-infiniteness, Convexity, and Politeness -- Decidability of difference logic over the reals with uninterpreted unary predicates -- Incremental Rewriting Modulo SMT -- Iscalc: an Interactive Symbolic Computation Framework (System Description).
Keywords: Artificial intelligence; Machine theory; Computer science; Software engineering; Artificial Intelligence; Formal Languages and Automata Theory; Computer Science Logic and Foundations of Programming; Software Engineering